Alum and PACl Coagulation - Winarni, Winarni (Makara Journal of Technology, 2003)
Alum and PACl Coagulation. Coagulation occurs by interaction of aluminum hydrolysis products with the contaminant such as colloidal particles. It is necessary to consider the different aluminum species that may present during specific conditions, since the mechanism of turbidity removal is dependent upon them. PACl consists of preformed aluminum hydrolysis products, which are stable below pH 6 and less sensitive than in situ hydrolysis product, alum. The benefits of PACl relative to alum have been investigated as a function of pH and Al dosages. Specific conditions and aluminum species that exist during the certain mechanisms of coagulation are discussed. Results suggest that PACl is more effective than alum in lower pH range and high pH range, whereas alum is optimum in the neutral condition.